Impairment of thermoregulation and performance via mild dehydration in ice hockey goaltenders - McCarthy, D. G.; Wickham, K. A.; Vermeulen, T. F.; Nyman, D. L.; Ferth, J.; Pereira, J. M.; Larson, D. J.; Burr, J. F.; Spriet, L. L. (International Journal of Sports Physiology and Performance, 2020)
During play, ice hockey goaltenders routinely dehydrate through sweating and lose =2% body mass, which may impair thermoregulation and performance. Purpose: This randomized, crossover study examined the effects of mild dehydration on goaltender on-ice thermoregulation, heart rate, fatigue, and performance. Methods: Eleven goaltenders played a 70-minute scrimmage followed by a shootout and drills to analyze reaction time and movements. On ice, they either consumed no fluid (NF) and lost 2.4% (0.3%) body mass or maintained body mass with water (WAT) or a carbohydrate-electrolyte solution (CES). Save percentage, rating of perceived exertion, heart rate, and core temperature were recorded throughout, and a postskate questionnaire assessed perceived fatigue. Results: Relative to NF, intake of both fluids decreased heart rate (interaction: P=.03), core temperature (peak NF=39.0°C [0.1°C], WAT=38.6°C [0.1°C], and CES=38.5°C [0.1°C]; P=.005), and rating of perceived exertion in the scrimmage (post hoc: P<.04), as well as increasing save percentage in the final 10 minutes of scrimmage (NF=75.8% [1.9%], WAT=81.7% [2.3%], and CES=81.3% [2.3%], post hoc: P<.04). In drills, movement speed (post hoc: P<.05) and reaction time (post hoc: P<.04) were slower in the NF versus both fluid conditions. Intake of either fluid similarly reduced postskate questionnaire scores (condition: P<.0001). Only CES significantly reduced rating of perceived exertion in drills (post hoc: P<.05) and increased peak movement power versus NF (post hoc: P=.02). Shootout save percentage was similar between conditions (P=.37). Conclusions: Mild dehydration increased physiological strain and fatigue and decreased ice hockey goaltender performance versus maintaining hydration. Also, maintaining hydration with a CES versus WAT may further reduce perceived fatigue and positively affect movements.